Cerebral death: diagnostic aspects - Manni, C.; Proietti, R.; Della Corte, F. (Medicina e Morale, 1993)
The authors consider that bad scientific popularization harms the public debate on so-called "cerebral death", and they study the biological concept of death. They observe that the discussions and confusion regarding death are mainly about two points: 1. the identification of cerebral death with the death of the person; 2. the criteria that have to be accepted for a correct diagnosis of cerebral death. The artide then proposes to clarify the possible misunderstandings of terminology and concepts in this difficult area. The mechanisms and the anatomical and clinical correlations of cerebral death are also studied with an illustration of the procedures of determination of death (from the classical to the most advanced) both in the adult and in the child.